The Many Faces of Poverty: Quantifying the deprivation costs of the 2001-2002 crisis in Argentina - Conconi, Adriana (2010)
This paper presents empirical evidence on the deprivation costs of the Argentinean crisis of 2001-2002. The approach to deprivation is multidimensional and focuses on four aspects of livelihood: labor, assets, education and income. These dimensions are constructed by multivariate data reduction techniques and then aggregated using Bourguignon and Chakravarty’s multidimensional poverty measure. The main findings indicate that the crisis had its greatest costs on well-being dimensions which are tied to the economic cycle, such as income and labor. On the other hand, costs are mild on structural aspects of well-being, such as assets and education. A sensitivity analysis shows that these results are found to be robust to different deprivation lines.